Experience of cladribine tablets usage in the treatment of multiple sclerosis in the Multiple Sclerosis Centre of the Khanty-Mansi Autonomous Area — Yugra - A. A. Sokolova; L. I. Anischenko; L. S. Zemlyanushin; E. A. Rubtsova (Неврология, нейропсихиатрия, психосоматика)
Cladribine is a tablet preparation for the treatment of relapsing-remitting multiple sclerosis (RRMS), which is used as an immune reconstitution therapy. A population-based cohort study was conducted in 54 patients with RRMS who received cladribine tablets.Objective: to evaluate our own experience of treating patients with highly active MS (HAMS) with cladribine tablets in real-life clinical practice in the MS Centre of the Khanty-Mansi Autonomous Area (KhMAA) — Yugra.Material and methods. The data source is the register of MS patients of the KhMAA — Yugra. Cladribine tablets at a dose of 3.5 mg/kg of body weight were prescribed in two annual treatment cycles, each comprising 2 weeks with a treatment duration of 4—5 days — at the beginning of the first month and at the beginning of the second month. In 2021—2023, 54patients received therapy with cladribine tablets with an average frequency of exacerbations of 1.2 (62 exacerbations in 48 patients) within 12 months prior to therapy initiation. Before starting therapy and every 6 months thereafter, patients underwent magnetic resonance imaging (MRI) of the brain, cervical and thoracic regions MRI with contrast enhancement, assessment of neurological status using the Expanded Disability Status Scale (EDSS), complete blood count, monitoring of blood lymphocytes level and biochemical blood testing. After the first and second treatment courses with cladribine tablets, the lymphocyte level was assessed after 2 months and after 6 months.Results. It was found that the average frequency of exacerbations before the start of treatment was 1.2 per year; after treatment with cladribine tablets it was 0.05 per year, i.e. the average annual frequency of exacerbations fell by 92% in the first year of treatment. Before starting treatment with cladribine tablets, only six (11%) out of 54 patients had no exacerbations; after starting the treatment with cladribine tablets, 48 (89.5%) patients had no exacerbations. The results obtained exceed the results of the CLARITY study, in which the proportion of patients without exacerbations in the cladribine group was 79.7%. In addition, all patients had no disease activity on MRI after starting cladribine therapy compared to the baseline data before starting cladribine therapy, when Gd+ lesions were detected on T1-weighted images in 50 (92.5%) patients. There was also no increase in disability. The mean EDSS score remained stable (median 3.0) or decreased by 0.5—1 point. At the end of follow-up period, 49 (92%) out of 54 patients included in the analysis achieved NEDA-3 status. No adverse events were observed during patient follow-up.Conclusion. The experience with the use of cladribine in KhMAA is consistent with data from real-world clinical practice around the world in terms of efficacy, safety and results of randomized clinical trials. Cladribine tablets are a highly effective and safe treatment for HAMS. Further monitoring of patients is required to assess the long-term benefits and risks of cladribine.